Pengaruh Audit Internal, Dan Pengendalian Internal, Terhadap Good Corporate Governance (Studi Kasus PTPN VI) - Muhammad Syahratul Ikhsan; Ratih Kusumastuti; Susfa Yetti (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2023)
Good Corporate Governance plays an important role in facilitating long-term growth, profitability and competitive advantage of companies in the global business landscape. Especially for organizations that have embraced transparency and openness, strong corporate governance practices serve as a shield against the common challenges that companies face in the contemporary business environment. Therefore, in accordance with this perspective, State-Owned Enterprises (BUMN) must also have the ability to adhere to the principles of Corporate Governance (Sanjaya et al., 2016).